Islands of change vs. islands of disaster: Managing pigs and birds in the Anthropocene of the North Atlantic. (October 2015) - Brewington, Seth; Hicks, Megan; Edwald, Ágústa; Einarsson, Árni; Anamthawat-Jónsson, Kesara; Cook, Gordon; Ascough, Philippa; Sayle, Kerry L; Arge, Símun V; Church, Mike; Bond, Julie; Dockrill, Steve; et al.
The offshore islands of the North Atlantic were among some of the last settled places on earth, with humans reaching the Faroes and Iceland in the late Iron Age and Viking period. While older accounts emphasizing deforestation and soil erosion have presented this story of island colonization as yet another social–ecological disaster, recent archaeological and paleoenvironmental research combined with environmental history, environmental humanities, and bioscience is providing a more complex understanding of long-term human ecodynamics in these northern islands. An ongoing interdisciplinary investigation of the management of domestic pigs and wild bird populations in Faroes and Iceland is presented as an example of sustained resource management using local and traditional knowledge to create structures for successful wild fowl management on the millennial scale.